Comparative anatomy of the larynx of the minke whale, Balaenoptera acutorostrata and the pygmy right whale, Caperea marginata - Best, Peter B. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2006.